IDENTIFICATION MORPHOLOGY DIFFERENTIATION BETWEEN MALE AND FEMALE SWAMP EEL Monopterus albus (Zuiew, 1793) BY TRUSS MORPHOMETRICS - Nova, Theresia Santika Deska; Yudha, Indra Gumay; Adiputra, Yudha Trinoegraha (Jurnal Perikanan Unram, 2020)
Swamp eel Monopterus albus (Zuiew, 1793) breeding was not developed due to limitation of technology. Swamp eel hatchery development may start with male and female eel brood stock differentiation with develop practical method base on morphology. Research conducted to identify morphology differentiation between male and female swamp eel applied truss morphometrics. One hundred male and female swamp eel were used and 18 phenotype characters were measured within head, body and tail parts. Results showed there were 10 phenotype characters able to use as a marker to distinguished male and female swamp eel. Five phenotype characters showed male swamp eel were bigger in size than female swamp eel, included anterior nostril, long of upper jaws to posterior nostril, mouth deep, body and total length. Moreover, five phenotype characters also showed that male swamp eel smaller in compared to female, included length of mouth to posterior of operculum, upper jaws length, head length, vent body width and tail length. In practical, ventral -dorsal of head part able to use as a marker of male swamp eel, in specify characters deep mouth width and stronger jaws appearance. However, female swamp eel was distinguished from longer tail length that related to preparation of gonadal development while adult phase. Body part of male and female swamp eel not able to use as sex marker.